2011
DOI: 10.1002/hep.24315
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage therapy for murine liver fibrosis recruits host effector cells improving fibrosis, regeneration, and function

Abstract: Clinical studies of bone marrow (BM) cell therapy for liver cirrhosis are under way but the mechanisms of benefit remain undefined. Cells of the monocyte‐macrophage lineage have key roles in the development and resolution of liver fibrosis. Therefore, we tested the therapeutic effects of these cells on murine liver fibrosis. Advanced liver fibrosis was induced in female mice by chronic administration of carbon tetrachloride. Unmanipulated, syngeneic macrophages, their specific BM precursors, or unfractionated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
304
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 286 publications
(328 citation statements)
references
References 33 publications
(91 reference statements)
18
304
3
Order By: Relevance
“…Infusion of bone marrow‐derived macrophages has been shown to reduce hepatic fibrosis by recruiting endogenous macrophages and neutrophils 3. Administration of granulocyte colony‐stimulating factor enhanced migration of bone marrow cells into fibrotic liver and accelerated the regression of liver fibrosis 24.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Infusion of bone marrow‐derived macrophages has been shown to reduce hepatic fibrosis by recruiting endogenous macrophages and neutrophils 3. Administration of granulocyte colony‐stimulating factor enhanced migration of bone marrow cells into fibrotic liver and accelerated the regression of liver fibrosis 24.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism underlying the positive effect of MSCs or macrophages on cirrhosis remains unknown, although several possibilities have been considered; these include transdifferentiation of MSCs into hepatocyte‐like cells, secretion of factors that suppress activated stellate cells, modulation of immunity, resolution of fibrosis, and stimulation of hepatocyte proliferation. On the other hand, it has been shown that bone marrow‐derived macrophage delivery induced up‐regulation of a chemokine that recruits endogenous macrophages and neutrophils in the liver, improving fibrosis 3. Furthermore, hepatic macrophages have been reported to promote the neutrophil‐dependent resolution of fibrosis in cholestatic rat liver 29…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier reports that BMCs could themselves adopt an epithelial phenotype in the liver have proven to be unfounded (24). A recent study by us in a chronic liver injury model has shown infusion of BM-derived macrophages improves fibrosis and is associated with improved liver function (22). However, a direct effect of macrophages upon the DRs or HPCs themselves has not been shown.…”
mentioning
confidence: 98%
“…Nonetheless, interpretation of a direct paracrine pathway from BM-derived cells to tissue progenitor cells is complicated during tissue injury by the association of local inflammation and tissue remodeling, processes that are affected by BM-derived cells (21,22) and that also indirectly influence tissue progenitor cell activation (23).…”
mentioning
confidence: 99%